PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PLOTAGON PADA MATA PELAJARAN BAHASA INDONESIA UNTUK SISWA KELAS IV SD NEGERI LUBUK KUMBUNG - Elya Rosalina; Tri Juli Hajani; Yuyani Yuyani (Primary Education Journal Silampari (PEJS), 2023)
This study aims to make a plotagon-based learning video media for fourth grade students of SD Negeri Lubuk Kumbung Musi Rawas which is valid and practical. Rawas age with a sample of 10 students for the small group test. The type of development used is the type of development of the 4D model (four-D model). The data collection technique used a validation questionnaire of linguists, material experts and practicality questionnaires for teachers and students. Based on the results of research and development, several conclusions can be drawn as follows: 1) Based on the results of the validation, it is known that the plotagon-based learning video is categorized as good with a validity percentage of 86,26 so it is categorized as valid. 2) The practicality of plotagon-based learning videos in individual trials or one to one involving 10 students is categorized as very good with a percentage of 91.33%. Based on the test results, it is known that the student responses are categorized as good, which means that the plotagon-based learning videos are practical or easy to use. Keywords: learning video, plotagon